2021
DOI: 10.1109/access.2021.3072420
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Prediction in Vessel Heave Motion Based on Improved LSTM Model

Abstract: In order to solve the problem of control performance degradation caused by time delay in wave compensation control system, predicting vessel heave motion can be the input vector of the control system to alleviate time delay problem. The vessel heave motion belongs to the problem of time series, this paper proposes an improved Long Short-Term Memory (LSTM) model with a random deactivation layer (dropout), which can deal with the time series problem very well. In order to obtain the vessel heave motion, this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…With the rise of neural networks in the past few years, several works utilize deep learning techniques to predict the behavior of vessels. These works may focus on different aspects of movement at sea from predicting a vessel's heave motion [36] to providing an estimate about future vessel traffic flow over an area [37]- [39]. Similarly, a number of frameworks that take advantage of their capabilities for effective trajectory forecasting have been proposed in recent years [40].…”
Section: ) Deep Learning For Vessel Trajectory Analysismentioning
confidence: 99%
“…With the rise of neural networks in the past few years, several works utilize deep learning techniques to predict the behavior of vessels. These works may focus on different aspects of movement at sea from predicting a vessel's heave motion [36] to providing an estimate about future vessel traffic flow over an area [37]- [39]. Similarly, a number of frameworks that take advantage of their capabilities for effective trajectory forecasting have been proposed in recent years [40].…”
Section: ) Deep Learning For Vessel Trajectory Analysismentioning
confidence: 99%
“…In short, this trend is constructed on extracting statistical features, statistical moments, frequency, or spectral-temporal features, handcrafting salient features from data then fitting them to a nonlinear regressors. Many studies can be named in all areas of science that deal with time series prediction and have inspired the ship response context, such as [16], where an improved Long Short-Term Memory (LSTM) model was adapted for short-term heave prediction, and the heave responses accurately predicted for 2s time span. Also, in a series of studies, Khan and colleagues demonstrated the efficiency of Artificial Neural Networks (ANN) for predicting ship motions for up to 8 seconds with reasonable uncertainties [17] and [18].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [15], a short‐term heave motion prediction scheme was proposed using an improved LSTM model. In Ref.…”
Section: Introductionmentioning
confidence: 99%